اثر الرضا الوظيفي لدى معلمي مدارس التعليم الأساسي، الحلقة الثانية (5-10) بسلطنة عمان = The effect of job satisfaction on organizational commitment among schools’ teachers (5-10) in Oman - Rashid, Said; Al-Hidabi, Dawood Abdulmalek Yahya; Abdulwahab Aldaba, Abdulmajid Mohammed (Multi-knowledge Electronic Comprehensive Journal For Education And Science Publications (MECSJ), 2020)
هدف هذا البحث إلى اختبار أثر الرضا الوظيفي في الالتزام التنظيمي لدى معلمي مدارس التعليم الاساسي الحلقة الثانية (5-10)بسلطنة عمان ، حيث اعتمد الباحثون في هذة الدراسة المنهج المسحي الوصفي الذي يعد منهجًا ملائمًا لطبيعة هذه الدراسة وأهدافها، وطبقًا لطبيعة الدراسة فقد استخدم الباحث في جمع بيانات هذه البحث المنهج الكمي مستخدما الطريقة المستعرضة (cross-sectional) في جمع بيانات البحث، مسخدما استبانة مكونه من (69) فقرة لجمع البيانات المتعلقة بمتغيرات الدراسة، وتم توزيعها على عينة دراسية بلغ عددها (1000) معلم ومعلمة في سبع محافظات تعليمية بسلطنة عمان، تم اختيارهم باستخدام العينه الطبقة العشوائية، وتمكن الباحث من الحصول هلى (846)استبانة صالحة للتحليل الاحصائي منها (419) معلما، و (427) معلمة، وتم ادخالها في برنامج (24 SPSS Version ) لاجراء التحليلات الزصفية، كما تم استخدام (AMOS Version 24 ) لاجراء التحليل العالمي التوكيدي (CFA ) لتقييم صدق البيانات وثباتها، كما تم استخدام برنامج AMOS لدراسة العلاقات بين متغيرات الدراسة، حيث كشفت نتائج الدراسة عن وجود تأثير مباشر للرضا الوظيفي على الالتزام التنظيمي، كما أظهرت النتائج وجود تأثير تفاعلي لمتغير المؤهل العلمي في العلاقة بين الرضا الوظيفي والالتزام التنظيمي فيما لا يوجد تأثير تفاعلي لمتغيري النوع الاجتماعي وسنوات الخبرة وقد تضمنت الدراسة عددًا من التوصيات والمقترحات للدراسات المستقبلية. **************************************************************************** The aim of this research was to examine the effect of job satisfaction on organizational commitment among teachers’ schools in Oman. The descriptive survey design was adopted in this quantitative study using cross-sectional method to collect data. A five likert-scale questionnaire consisting of (69) items was distributed amongst 1000 teachers in seven educational governorates in Oman. Stratified random sampling was employed to obtain (846) questionnaires, out these 846 participants 419 were males and 427 were males. SPSS version 26 was used to conduct the descriptive analysis, while AMOS (version 24) was used to perform confirmatory factor analysis (CFA) to assess the validity and reliability of this study model. AMOS was also used to examine the relationships between job satisfaction and organizational commitment. The results revealed a significant direct impact of job satisfaction on organizational commitment. It also showed that teachers’ qualification plays the role moderation role between job satisfaction and organizational commitment. However, both teachers’ gender and teaching experience do not exert any moderation effect between job satisfaction and organizational commitment. The study concluded with recommendations and suggestions for future studies.